Corporate Identity / Making Business Strategy Visible Through Design - Olins Wally; Thames And Hudson (1989)
A splendid exploration of how big business keeps itself in the public eye. The Invention of Tradition, The Corporate Search for Identity, Visual Style, Corporate Structure, Corporate Strategy, Creating an Identity Program and the First Stage, Creating an Identity Program and Managing Change, Launching and Maintaining an Identity Program, Corporate Identity and the Future, Select Bibliography, Author's and Illustration Acknowledgements.